Cryptic coral community composition across environmental gradients - Gia N. Cabacungan; Tharani N. Waduwara Kankanamalage; Amilah F. Azam; Madeleine R. Collins; Abigail R. Arratia; Alexandra N. Gutting; Mikhail V. Matz; Kristina L. Black (PLoS ONE, 2025)
Cryptic genetic variation is increasingly being identified in numerous coral species, with prior research indicating that different cryptic genetic lineages can exhibit varied responses to environmental changes. This suggests a potential link between cryptic coral lineages and local environmental conditions. In this study, we investigate how communities of cryptic coral lineages vary along environmental gradients. We began by identifying cryptic genetic lineages within six coral species sampled around St. Croix, USVI based on 2b-RAD sequencing data. We then analyzed associations between the distributions of cryptic lineages across the six coral species (i.e., “cryptic coral community composition”) and ecoregions, or geographically distinct environmental conditions. Our findings show that depth is a more significant predictor of community composition than ecoregions and is the most influential factor among the 40 abiotic variables that characterize ecoregions. These results imply that cryptic coral communities are influenced by both depth and local environmental conditions, although the exact environmental factors driving these patterns remain unknown. Understanding community turnover across a seascape is important to consider when outplanting corals to restore a reef, as locally-adapted lineages may have differential fitness in different environmental conditions.